BODY SIZE OF LOCAL BOAR GIVEN LYSINE, METHIONINE, AND CHOLINE ADDITIONAL SUPLEMENTATION IN RATIONS - N. N., Yuliyanti; Sumadi, I K.; Suasta, I M. (Jurnal Peternakan Tropika; Vol 6 No 2 (2018): May - August 2018, 2018)
This study aims to find out the effect of lysine, methionine, and choline supplementation in rations to body size of local boar. This study was conducted for 12 weeks at Taman Wedasari st, Batuparas area, Padang Sambian Kaja villege. Design of this study is used completely randomized design (CRD) was used in this study with 3 treatments and repetition. Those treatment were (A)ration with 0% supplementation of  lysine, methionine, and choline, (B) with 0,5%, and (C) with 1%. Each treatment was given to 3 local boar, every respetitions contained one boar pig local, in the other words this study is used 9 local boarl. Size parameters observed were chest circle, stomach circle, flank circle,shoulder height, spine height, hip heigh and length of the body. This study showed that those three treatment resulted in similar body size of local boar. It can be concluded that supplementation of lysine, methionine and choline as much as 0,5% and 1% give similar results as control on all of the body size observed. Keywords: Boar pig local, body size, supplementation ( mix of lysine, methionine, and choline)